2022
DOI: 10.1007/s00432-022-03915-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-profiling of miR-371~373- and miR-302/367-clusters in serum and cerebrospinal fluid identify patients with intracranial germ cell tumors

Abstract: Purpose Intracranial germ cell tumors (iGCT) comprise germinoma and non-germinoma. Their diagnosis predominantly relies on biopsy as only one-fifth of patients present with elevated biomarkers (AFP/ß-HCG) in serum or cerebrospinal fluid (CSF). MicroRNAs (miR/miRNA) have emerged as non-invasive biomarkers in extracranial GCT and may potentially facilitate non-invasive diagnosis in iGCT. Methods We analyzed eight miRNAs in serum and CSF from the miR-371~373-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
7
2
Order By: Relevance
“…In our samples, we were unable to detect the previously documented miR-371 ~ 373 and miR-302/367 clusters (Murray et al 2016). This is in contrast to a recent study by Schönberger et al, where they demonstrated the suitability of miR-371a, miR-372, miR-367 and miR-302d in serum and CSF for diagnosis of CNS GCT, particularly in biomarker-negative pure germinoma (Schönberger et al 2022). This discrepancy can be attributed to the difference in methodology between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our samples, we were unable to detect the previously documented miR-371 ~ 373 and miR-302/367 clusters (Murray et al 2016). This is in contrast to a recent study by Schönberger et al, where they demonstrated the suitability of miR-371a, miR-372, miR-367 and miR-302d in serum and CSF for diagnosis of CNS GCT, particularly in biomarker-negative pure germinoma (Schönberger et al 2022). This discrepancy can be attributed to the difference in methodology between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, in a global miRNA expression analysis of 12 tumor specimens from primary pediatric GCT of the brain, pure germinoma-speci c upregulation of miR-142-5p and miR-146a-5p was reported, in contrast to overexpression of miR-335-5p and miR-654-3p in NGGCT (Wang HW et al 2010). Yet, it is still unknown whether detection of these miRNAs are discriminatory in the serum/plasma of pediatric CNS germinoma patients (Schönberger et al 2022). We sought to identify plasma signatures that could distinguish pure germinomas of the pineal region from all other tumors in this area, thus potentially avoiding the need for surgical intervention in this very vulnerable part of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Within the scope of this study, we have not been able to incorporate novel biomarkers for CNS GCTs, such as CSF and serum microRNAs. Specific microRNA species allow differentiation between patients with and without CNS GCTs [48]. MicroRNA profiling may represent a powerful platform as serial monitoring allows the tracking of treatment responses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a global miRNA expression analysis of 12 tumor specimens from primary pediatric GCT of the brain, pure germinoma-specific upregulation of miR-142-5p and miR-146a-5p was reported, in contrast to overexpression of miR-335-5p and miR-654-3p in NGGCT ( 4 ). Yet, it is still unknown whether the detection of these miRNAs is discriminatory in the serum/plasma of pediatric CNS germinoma patients ( 21 ). We sought to identify plasma signatures that could distinguish pure germinomas of the pineal region from all other tumors in this area, thus potentially avoiding the need for surgical intervention in this very vulnerable part of the brain.…”
Section: Introductionmentioning
confidence: 99%